ANALYSIS OF CONSUMER BEHAVIOR OF FOREIGN MARKET BUSINESS FOR COMMODITY OF CASHEWS at PT GDK JAWABARAT - Elpy siti Nurhalimah; Supriyadi Supriyadi; Rani Siti Fitriani; Raden Willa Permatasari (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this research is to examine 1. What factors attract foreign buyers to import cashew nuts from Indonesia?.2. What are the obstacles faced by foreign buyers in the process of importing cashew nuts from Indonesia?.3. What are the stages of the process carried out by buyers to import cashews from Indonesia?.4. What is the solution to these obstacles? This research was made using a qualitative descriptive analysis type of research regarding the marketing process of the cashew nut export sales business. (2) Currency differences. (3) Obstacles in the Form of Regulations. (4) International trade barriers are seen from economic institutions, namely: The influence of economic organizations, Anti-dumping regulations that increase import duty rates, Embargoes related to the prohibition of trade between countries. What is the solution to these obstacles? (1). Solution for difficult payments, by L/C. (2) The solution when the currency, using the USA currency or by agreement, is exchanged to the value of the destination country. (3) The solution to obstacles in the form of regulation, is to instinctively follow market trends. (4) Solutions to barriers to economic institutions, exporters take advantage of facilities from countries that are members of economic organizations, export at competitive prices, and resolve trade embargo issues between countries.